(untitled) (Literatures of the World: Poetics, Mentality and Spirituality, 2018)
The article deals with the phonetic system of the Ukrainian and Spanish languages on the example of Spanish translations of poetry “Kobzar” by Taras Shevchenko. This paper investigates the strategies of phonetic and phonemic recombinations of translation, that contribute to the Ukrainian identity reproduction in Spanish. The research states that the reflection of Ukrainian euphony, in particular the language of Taras Shevchenko, excites due to phonetic, grammatical, syntactic and semantic reconstruction of language units. It also determines that the ethnic paradigm encoded into the language worldview of Ukrainians is explicated in Spanish by preserving ethnic symbols in their phonetic and / or lexical and semantic interpretation. Moreover, it states that the reproduction of rhythm and melody in the poetry of T. Shevchenko is fragmentary in Spanish translation. It is possible due to the structural elasticity and the euphony of the Spanish language. The other reason is connected with synthetic origin of Ukrainian and analytical nature of Spanish. It should be mentioned that even though the special selection of the proper vocabulary, which is not similar to syllabic system of the original poems, allows creating close mimic sounding of rhythms in Shevchenko poetry. In fact, the impossible reproduction is observed at the level of letter combination, since the letters in each language of the world have their own emotional and semantic characteristics, dependent on mentality. During the analysis of the syllabic and tone system of original verse writing in Taras Shevchenko poetry and its Spanish translation, a phonetic universality of the writer’s works is discovered, which is characterized by a tonal manifestation.